2009
DOI: 10.1111/j.1468-0084.2008.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Explanation of the Forecast Combination Puzzle*

Abstract: This article presents a formal explanation of the forecast combination puzzle, that simple combinations of point forecasts are repeatedly found to outperform sophisticated weighted combinations in empirical applications. The explanation lies in the effect of finite-sample error in estimating the combining weights. A small Monte Carlo study and a reappraisal of an empirical study by Stock and Watson ["Federal Reserve Bank of Richmond Economic Quarterly" (2003) Vol. 89/3, pp. 71-90] support this explanation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
145
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(158 citation statements)
references
References 18 publications
7
145
1
Order By: Relevance
“…Several studies have shown that, due to the effect of finite-sample error in estimating the combining weights, an equally weighted mean is often the best choice (Makridakis and Winkler, 1983;Clemen, 1989;Watson, 2001, 2004;Smith and Wallis, 2009). We follow this conclusion and in the rest of the paper we assume θ k = 1/K.…”
Section: Combining Forecastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that, due to the effect of finite-sample error in estimating the combining weights, an equally weighted mean is often the best choice (Makridakis and Winkler, 1983;Clemen, 1989;Watson, 2001, 2004;Smith and Wallis, 2009). We follow this conclusion and in the rest of the paper we assume θ k = 1/K.…”
Section: Combining Forecastsmentioning
confidence: 99%
“…Methods of increasing sophistication followed the simple adaptive time series approach of Bates and Granger (1969), including Bayesian (Bunn, 1975(Bunn, , 1977, and econometric (Granger and Ramanathan, 1984), as well as extensions to large data sets Watson, 2001, 2004), but, for robust forecasting, it has appeared hard to improve upon simple averaging (Makridakis and Winkler, 1983;Clemen, 1989;Watson, 2001, 2004;Smith and Wallis, 2009). We therefore do not address the question of developing combining methods to improve on simple averaging.…”
Section: Introductionmentioning
confidence: 99%
“…We have few observations, so the so-called "forecast combination puzzle" (the fact that the sample average of forecasts gives better forecasting results than more sophisticated weighting schemes) might arise. See, for instance, Smith and Wallis (2009) and Aiolfi, Capistrán and Timmermann (2011). We would like to suggest forecast combination procedures that might work better in situations in which the sample is quite short.…”
Section: Mexico: Combining Monthly Inflation Predictions From Surveysmentioning
confidence: 99%
“…With regard to forecast combination, Capistran and Timmermann (2009), as well as Timmermann (2004, 2005), estimate combination weights by minimizing a given loss function, ensuring that the weights converge to those minimizing expected loss. Wallis (2005) proposes combining forecasts using a finite mixture distribution, and Smith and Wallis (2009) suggest the use of simple averages. With regard to rationality assessment, Elliott, Komunjer and Timmermann (2008) test whether forecasters taking part in the SPF are rational for some parameterization of a flexible loss function.…”
Section: Motivationmentioning
confidence: 99%